(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In Lisa See’s Peony in Love, the love-sick lady Peony undergoes anorexia which ultimately ends in her death. Anorexia and foot binding are the deformities of the female body and these abnormalities use numerous symbols to communicate.